The dialectic relation between the national and the European constitutional identity in the framework of European Constitutional Law - Balaguer Callejón, Francisco (2017)
This article intends to reflect on the concept of constitutional identities of states in the frame of the dialectic relationship between the legal order of the European Union and the national legal orders. Both the conflictual dimension of the constitutional identity and the relations of confluence that that can maximize are explored. It concludes with an open and flexible understanding of the concept of constitutional identity which can benefit the evolution of the national constitutional law in an Europeist sense and the progressive transformation of the European legal system in a constitutional sense.